A β-Hairpin motif in the envelope protein E2 mediates receptor binding of bovine viral diarrhea virus - Merwaiss, Fernando (2021)
Pestivirus envelope protein E2 is crucial to virus infection and accomplishes virus-receptor interaction during entry. However, mapping of E2 residues mediating these interactions has remained unexplored. In this study, to investigate the structure-function relationship for a β-hairpin motif exposed to the solvent in the crystal structure of bovine viral diarrhea virus (BVDV) E2, we designed two amino acidic substitutions that result in a change of electrostatic potential. First, using wild type and mutant E2 expressed as soluble recombinant proteins, we found that the mutant protein had reduced binding to susceptible cells compared to wild type and diminished ability to inhibit BVDV infection, suggesting a lower affinity for BVDV receptors. We then analyzed the effect of β-hairpin mutations in the context of recombinant viral particles. Mutant viruses recovered from cell culture supernatant after transfection of recombinant RNA had almost completely inhibited ability to re-infect susceptible cells, indicating an impact of mutations on BVDV infectivity. Finally, sequential passaging of the mutant virus resulted in the selection of a viral population in which β-hairpin mutations reverted to the wild type sequence to restore infectivity. Taken together, our results show that this conserved region of the E2 protein is critical for the interaction with host cell receptors.